DIGITALISASI ADMINISTRASI PAJAK DAN DAMPAKNYA TERHADAP KEPATUHAN UMK DI KOTA BANDUNG - Gunardi, Gunardi; Febriani, Eri; Kurniawan, Sandy; Framesthi, Dyah Bayu (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2025)
This study aims to analyze the impact of tax administration digitalization on the tax compliance of Micro and Small Enterprises (MSEs) in Bandung City. Using a Systematic Literature Review (SLR) approach, the research examines the implementation of digital systems such as e-filing, e-billing, and DJP Online, along with the challenges faced by MSEs. The findings show that while digitalization offers improved access and administrative efficiency, the overall tax compliance rate among MSEs remains low—only 38.1% in 2023. Key barriers include low tax and digital literacy, limited outreach and support, unequal access to technology, and negative perceptions of taxation. Conversely, digitally savvy MSEs tend to report higher compliance and enjoy additional benefits, such as access to business financing and enhanced reputation. The study recommends strengthening education, digital infrastructure, and government support to improve compliance. The findings are expected to inform more inclusive policy-making and contribute to optimizing tax revenue from the MSE sector in the digital era.